Expediente, v. 1, n. 1, jan./jun., 2021 - Revista de Produção Editorial, Gutenberg - (Gutenberg - Revista de Produção Editorial, 2021)
Expediente da Gutenberg - Revista de Produção Editorial, Santa Maria, RS, Brasil, v. 1, n. 1, jan./jun., 2021.